'The experience of spirituality in family caregivers of adult and elderly cancer patients receiving palliative care: A meta‐synthesis'. (5th February 2021) - Benites, Andrea Carolina; Rodin, Gary; Leite, Ana Carolina Andrade Biaggi; Nascimento, Lucila Castanheira; dos Santos, Manoel Antônio
Abstract: Introduction: Spirituality is a multidimensional aspect of human experience. In the context of palliative care, it is an individual resource that can be used to cope with illness and to assign new meanings to suffering. Qualitative studies that aim to investigate the experience of spirituality and the needs of family caregivers in this context are rare. Objective: This meta‐synthesis aimed to synthesise qualitative studies on the experience of spirituality in family caregivers of adult and elderly cancer patients receiving palliative care. Methods: A systematic review was performed in six databases, and 14 studies were included in this meta‐synthesis. Results: The results are presented as a thematic synthesis divided into two analytical themes: (1) The interweaving of spirituality with end‐of‐life care and (2) The dimensions of suffering and spirituality in the dying process of the loved one. Each analytical theme is explained by two descriptive themes. The results showed that family caregivers express their spirituality in a multidimensional way, giving meaning to the care provided and reassessing the meanings of their lives and their suffering. Conclusion: Investigating the suffering and spiritual needs of family members in this context may be of value to inform comprehensive and multi‐professional psychosocial care.